THE APPLICATION OF HUMANISTIC LEARNING THEORY TO THE STUDY OF ISLAMIC RELIGIOUS EDUCATION IN ELEMENTARY SCHOOLS - Darmanto; Yusron Hanafi (Global Action and Education for Society, 2025)
The process of learning is cognitive, affective, and psychomotor changes. Learning theories that are in accordance with the characteristics of each educational institution are very important in the process of learning. Understanding the integration of humanistic learning theory into Islamic Religious Education is the aim of this work. Data for this qualitative study was gathered through interviews, documentation, and observation. The study's findings show that humanistic learning theory forms the foundation of SDIT Alam Nurul Islam Ngawi's Islamic Religious Education curriculum. This is evident in the ways that educational activities are implemented in schools, the learning design that is employed, and the conduct of the students. These exercises have a beneficial effect on students' psychological growth since they are human beings, not machines that may be taught to fit the skills of teachers. Therefore, the goal of humanistic learning theory is to comprehend human nature. This educational theory has changed the education system from being centered on teachers to being centered on students, meaning that teachers only act as facilitators.